Perancangan Manual SMK3 Berdasarkan ISO 45001 Tahun 2018 Klausul 8 dan 9 Di Universitas “X” - Yoshua Limanto; Jani Rahardjo (Jurnal Titra, 2022)
Occupational safety and health (OS&H) is an important factor to be implemented and carried out in a company. “X” university wants to provide a sense of security, comfort, and health to all of its civitas, by designing a SMK3 manual based on ISO 45001:2018. Before (OS&H) is implemented, it is necessary to have a design first. There is an internasional organization that discusses standardization related to occupational safety and health, namely ISO 45001 in 2018. The design is carried out by observing the “X” University environment, collecting data, determining the requirements of ISO 45001:2018 clauses 8 and 9, auditing data by comparing university conditions with standards ISO 45001:2018 clauses 8 and 9, designing a manual for the SMK3 management system with the requirements of ISO 45001:2018 clauses 8 and 9, and conducting validation. Before designing, “X” University have nineteen Standard Operating Procedure (SOP) and four supporting forms. After designing, “X” University has twenty eight SOP and four supporting forms.